2000
DOI: 10.1046/j.1464-410x.2000.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic device for increasing the urethral resistance to flow: an experimental study in female dogs

Abstract: Objective To test a new magnetic device for increasing the urethral resistance to¯ow in a dog model, and thus provide a potential mechanical device for the treatment of incontinence in women. Materials and methods The study comprised 12 female mongrel dogs; three dogs were used to study the effect on urethral resistance of inserting a vaginal magnet (control experiment) and ®ve were assessed in a urodynamic study. With the animals under general anaesthesia, the bladder and the urethra were exposed by a low mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…No histologic evidence of vascular congestion or edema was detected in the transitional epithelium, lamina propria, muscularis mucosa or tunica muscularis but some was present in the serosa. The total irritation index score was 5 which indicated a mild irritative response [10-11]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No histologic evidence of vascular congestion or edema was detected in the transitional epithelium, lamina propria, muscularis mucosa or tunica muscularis but some was present in the serosa. The total irritation index score was 5 which indicated a mild irritative response [10-11]. …”
Section: Resultsmentioning
confidence: 99%
“…After 2 weeks, the TMOD was activated (ON mode) except for night time and three times a day (30 minutes each) to simulate the natural voiding pattern of the animals. At 6 and 9 weeks post-implantation, following administration of appropriate anesthetics, the urethral sphincter was temporarily paralyzed in 3 female dogs with 0.1 mg/kg succinyl choline to simulate sphincter damage [10]. Urethral pressure profilometry was then performed by the catheter based perfusion method with TMODs ON & OFF.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of results of our study also confirmed our hypothesis that a simple, percutaneously controlled HUS could be used to improve urodynamic variables in canine cadavers. Although they will never supersede objective evaluation of clinical outcome in dogs with naturally developing USMI, urodynamic variables have served as 1 of the few objective means of comparing the effects of medical or surgical treatment in controlled studies 4,7,[24][25][26][27][28][29][30][31][32][33] and have been reported consistently in the veterinary literature. Studies 7,20,[25][26][27]29,30 of diagnostic or surgical techniques for USMI are often performed in clinically normal animals or on cadavers, making it impossible to quantify the degree of incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Although they will never supersede objective evaluation of clinical outcome in dogs with naturally developing USMI, urodynamic variables have served as 1 of the few objective means of comparing the effects of medical or surgical treatment in controlled studies 4,7,[24][25][26][27][28][29][30][31][32][33] and have been reported consistently in the veterinary literature. Studies 7,20,[25][26][27]29,30 of diagnostic or surgical techniques for USMI are often performed in clinically normal animals or on cadavers, making it impossible to quantify the degree of incontinence. Consequently, studies 7,20,[25][26][27]29 have often relied on urodynamic variables to describe the mechanism of action of medical and surgical interventions for USMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation